Effect of Pre-weaning Diet on the Ruminal Archaeal, Bacterial, and Fungal Communities of Dairy Calves - Dias, Juliana; Marcondes, Marcos I.; Noronha, Melline F.; Resende, Rafael T.; Machado, Fernanda S.; Mantovani, Hilário C.; Dill-McFarland, Kimberly A.; Suen, Garret (Frontiers in Microbiology, 2017)
At birth, calves display an underdeveloped rumen that eventually matures into a fully functional rumen as a result of solid food intake and microbial activity. However, little is known regarding the gradual impact of pre-weaning diet on the establishment of the rumen microbiota. Here, we employed next-generation sequencing to investigate the effects of the inclusion of starter concentrate (M: milk-fed versus MC: milk plus starter concentrate fed) on archaeal, bacterial and anaerobic fungal communities in the rumens of 45 crossbred dairy calves across pre-weaning development (7, 28, 49 and 63 days). Our results show that archaeal, bacterial and fungal taxa commonly found in the mature rumen were already established in the rumens of calves at 7 days old, regardless of diet. This confirms that microbiota colonization occurs in the absence of solid substrate. However, diet did significantly impact some microbial taxa. In the bacterial community, feeding starter concentrate promoted greater diversity of bacterial taxa known to degrade readily fermentable carbohydrates in the rumen (e.g. Megasphaera, Sharpea and Succinivribrio). Shifts in the ruminal bacterial community also correlated to changes in fermentation patterns that favored the colonization of Methanosphaera sp.A4 in the rumen of MC calves. In contrast, M calves displayed a bacterial community dominated by taxa able to utilize milk nutrients (e.g. Lactobacillus, Bacteroides and Parabacteroides). In both diet groups, the dominance of these milk-associated taxa decreased with age, suggesting that diet and age simultaneously drive changes in the structure and abundance of bacterial communities in the developing rumen. Changes in the composition and abundance of archaeal communities were attributed exclusively to diet, with more highly abundant Methanosphaera and less abundant Methanobrevibacter in MC calves. Finally, the fungal community was dominated by members of the genus SK3 and Caecomyces. Relative anaerobic fungal abundances did not change significantly in response to diet or age, likely due to high inter-animal variation and the low fiber content of starter concentrate. This study provides new insights into the colonization of archaea, bacteria and anaerobic fungi communities in pre-ruminant calves that may be useful in designing strategies to promote colonization of target communities to improve functional